2010
DOI: 10.1002/poc.1727
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthesis of 2‐aminoquinoline‐3‐carbaldehyde, benzo[b][1,8]naphthyridines and study of their fluorescence behavior

Abstract: A novel route was successfully developed for the synthesis of new synthons, orthoamino formyl quinoline (heterocyclic orthoaminoaldehyde) and utilized for the synthesis of series of benzonaphthyridines by Friedländer condensation reactions with benzoylacetonitrile. The benzonaphthyridines synthesized were further studied for their fluorescence properties. Copyright © 2010 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…We also obtained important material characteristics and compared them among molecules. Those were values of the HOMO (E HOMO ¼[ À 5,9; À 5,5] eV), the LUMO (E LUMO ¼[ À 3,6; À3] eV) energy levels together with optical band gap (E g_opt ¼[2; 2, 8] eV), Stokes' shift (Δλ Stokes' ¼ [64; 155] nm), differences between PL spectra in thin film and chloroform solution (Δλ PL ¼[ À42, 84] nm) and solvatochromism (comparing PL in toluene, chloroform and 2-methoxyethanol (Δλ ¼ [12,77] nm)). It was noticed, that the value of optical band gap E g increases (for all molecular size groups) with changing substituents in such order: amine (smallest E g ), tetrazole, iminophosphorane, chlorine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also obtained important material characteristics and compared them among molecules. Those were values of the HOMO (E HOMO ¼[ À 5,9; À 5,5] eV), the LUMO (E LUMO ¼[ À 3,6; À3] eV) energy levels together with optical band gap (E g_opt ¼[2; 2, 8] eV), Stokes' shift (Δλ Stokes' ¼ [64; 155] nm), differences between PL spectra in thin film and chloroform solution (Δλ PL ¼[ À42, 84] nm) and solvatochromism (comparing PL in toluene, chloroform and 2-methoxyethanol (Δλ ¼ [12,77] nm)). It was noticed, that the value of optical band gap E g increases (for all molecular size groups) with changing substituents in such order: amine (smallest E g ), tetrazole, iminophosphorane, chlorine.…”
Section: Discussionmentioning
confidence: 99%
“…Different investigated derivatives of quinoline were synthesized in the same manner (Scheme 1) [12].…”
Section: Synthesis Of Quinoline Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few of these composites exhibited good antimicrobial activity. Shelar et.al developed a novel route for the synthesis of ortho amino formyl quinoline (heterocyclic ortho amino aldehyde) which in turn was utilized for the synthesis of series of benzonaphthyridines which exhibited excellent fluorescent properties 32 .Over the years, the Vilsmeier-Haack (VH) reagent is used as an efficient, economical and mild reagent for the formylation of aromatic and heteroaromatic substrates. Basically, DMF and oxychloride under chilled conditions 33 in situ forms a chloromethyleniminium salt, which is used as a powerful synthetic tool to achieve several aromatic and heterocyclic compounds including quinoline derivatives [34][35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…From literature it was also noted that 1,8-naphthyridine derivatives were not only use as luminescence materials in molecular recognition because of their rigid planer structure [6][7][8], possess antibacterial [9], antymicobacterial [10], antitumoral [11], anti-inflammatory [12], antiplatelet [13], gastric antisecretary [14], antiallergic [15] and local anaesthetic [16]. Recently, our research group reported systematic studies about the fluorescence properties of differently substituted pyrazolofused heterocycles [17][18][19][20][21][22] and benzo naphthyridines [23][24][25][26]. Annulation reactions with hetrocyclic aminoaldehydes provides synthectic entry into hetrocyclic systems, fused to a pyridine or pyrimidine nucleus by Friedlander condensation reactions with reactive methylenes.…”
Section: Introductionmentioning
confidence: 99%